Ethical And Juridical Issues In Midwifery Malpractice Cases: An Ethicolegal Study - Dhita Yuniar Kristianingrum (International Journal of Health and Pharmaceutical (IJHP), 2024)
Medical malpractice is one of the branches of error in the professional field, especially in the world of health. in the professional field, especially in the world of health. Actions of Medical malpractice involving doctors and other health workers such as nurses and midwives is of many types and forms. The research method used is library legal research. The data used is The data used is secondary data obtained from textbooks, articles, opinions of experts and journals. The type of research in this thesis is qualitative research with a descriptive approach. Misconduct in obstetric procedures is one of the branches of misconduct in the professional field, within the professional field. There are many types and forms of errors in medical procedures involving doctors or midwifery. There are many types and forms of errors in medical procedures involving doctors and health workers such as midwives. Midwives in carrying out carrying out their duties are not infrequently protested by patients for making mistakes or being negligent which results in loss. Medical errors occur into 3 (three) of them are international professional misconduct, Negligence and Lack of Skill.